(untitled) (Journal of Dentistry and Allied Science, 2025)
Background: Information concerning the oral health status and prevalence of caries in Bangladeshi young adult is very limited and has been studied to a narrow extent. Method: The aim of the study to assess the prevalence of caries and DMFT/DMFS among young adult. For the purpose of this cross-sectional study 162 patients who attended to the outpatient department (OPD) in private dental college, at University Dental College and Hospital were selected. Data were collected through face-to-face interview and analyzed by SPSS version 21. Results: From this current study result I found that maximum (40%) of the respondents were in the group of 18-22 years with the mean age± SD was 25.950±5.666 and majorities (58.6%) were male where almost all (92.0%) were Muslim. Regarding maintenance of oral hygiene, maximum (56.8%) was never visited to the dental surgeon, all (100%) of them were brush their teeth and majorities (59.3%) were practice twice in a day where almost all (90.1%) rinse their mouth after eating sweetened food/ each meal. Almost all (95.7%) were used brush and paste as combined materials for teeth brushing and (58.6%) were brush their teeth by up and down stroke method. Maximum (43.2%) of the respondents liked fibrous food in their diet. After conducting intraoral examination, I had found that, maximum (45.7%) had mild dental plaque and All (100%) the respondents had calculus in their mouth. Majorities had no filling (56.2%), missing teeth (69.1%) and no caries (56.2%) among them maximum (56.3%) had suffered mostly by pit and fissure caries in oral cavity. So, the prevalence of caries in this study was 43.8%. In case of decayed surface, maximum (53.7%) had no decayed surface. Finally, after the calculation the total DMFT and DMFS of 162 respondents were 1.185 and 1. 209 was found as 1.209 which was >1 in both indices. Conclusion: Although the overall dental caries epidemiological picture among young adults in Dhaka was favorable since prevalence and severity was considered low when compared to the goals recommended by the Oral Health Organization and the studies which contrasted. Journal of Dentistry and Allied Science, Vol. 8 No 1: 43-46